Komunikasi dalam Kepemimpinan Berbasis Tim untuk Meningkatkan Kekompakan antar Bidang Pelayanan di Gereja Lokal - Caroline Sabatini Baiin; Beni Chandra Purba (PT. Penerbit Tiga Mutiara, 2024)
This research aims to explore the communication for importance of team-based leadership in enhancing cohesion among service departments in the church. By understanding the concept of leadership inspired by the example of Jesus Christ, this study examines explore how communication can realize implementation principles such as selfless love, service focused on the interests of others, and obedience to divine will become the primary pillars in guiding, inspiring, and managing team members towards achieving common goals. A literature analysis method is employed to explore the concepts of leadership and team collaboration in the context of church service. The research findings emphasize the importance of effective communication, deep understanding of individuals within the team, and productive collaboration as the main foundation in strengthening cohesion among service departments. By prioritizing clear communication, empathetic understanding of team member’s needs, and building solid working relationships, leaders can create an environment that supports spiritual growth and unity in church service. In conclusion, leaders and team members can synergistically and effectively align their efforts to achieve the church’s vision and mission through leadership practices centered on love, effective communication, and solid team collaboration.